Kajian Ragam Material Rotan Dengan Sistem Modular Pada Interior Bangunan Residensial - Astuti, Anggi Dwi (Program Studi Desain Interior Unikom, 2023)
Rattan is one of the main materials in simple crafts and interior furniture items. Rattan also has economic value as a commercially viable product. The gradual decline in rattan production is increasingly visible both at home and abroad as a result of product marketing diversification having to target larger markets. Diversification of rattan products also benefits young designers by increasing their opportunities and competition in producing decorative panel designs made from local rattan. This research explores the various types of rattan materials available and identifies the unique characteristics of each type of rattan and their potential in modular design, so that rattan panels become one of the right renewable solutions to increase the absorbency of rattan materials with more efficient manufacturing techniques. The interior aesthetic benefits of rattan-based room dividers are projected to be utilized in various interior components to enhance the image of connected items and support local nuances in a more modern dressing, in line with the rise of residential buildings. Through this work, it is hoped that it can become a source of knowledge for students and can compete both aesthetically and functionally.